Challenges and opportunities to include patient‐centric product design in industrial medicines development to improve therapeutic goals. Issue 10 (16th June 2020) - Timpe, Carsten; Stegemann, Sven; Barrett, Andrew; Mujumdar, Siddharthya
Abstract : In the past, drug developers in industry chose approaches mainly focusing on the drug product's efficacy, safety and quality according to the level required by regulatory expectations stipulated in guidelines, pharmacopoeia and other regulatory provisions. By putting more focus on the patient perspective, regulatory authorities are currently raising their requirements regarding successful product submissions. The increasing involvement of patients in the product development process (e.g. conduction of human factor use tests, integration of feedback from patient and patient advisory groups into clinical programmes) requires adaptations to the existing and established industrial drug development processes without compromising fast patient access to innovative therapies. This review provides an expert opinion on the emerging challenges and opportunities to implement a patient‐centric approach into new drug development programmes. The aim is to better understand the challenge of finding the right balance between bringing innovative drugs fast to the patients and to develop these in parallel in a patient‐centric product form as well as why this is an opportunity and how stakeholder parties (e.g. patients, clinicians, pharmacists, caregivers, regulators) can provide support to achieve desired outcomes.